Nitrogen management practices for improving yield and nitrogen use efficiency in rice (Oryza sativa) - Verma, Rahul Kumar; Singh, Adesh; Hasanain, Mohammad; Raza, Md Basit; Singh, Rajiv Kumar (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted on rice (Oryza sativa L.) during kharif season of 2017 at Crop Research Centre of Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut (U P) to assess the nitrogen (N) use efficiency and performance of rice under different nitrogen management practice. Management practices included N levels with modified application through leaf colour chart (LCC) and chlorophyll meter (SPAD). The study shows that treatment T6 (LCC (50 kg N/ha) with basal N @50 kg/ha)gave highest yield and N-use efficiency which were comparable to T9 (SPAD (67 kg N/ha) with basal N @33 kg/ha). The total biological yield (grain + straw) of rice was significantly higher in T6 (114.4 q/ha) as compared to control (66.9 q/ha). The SPAD and LCC-treated plot showed higher N-use efficiency in rice over fixed-scheduling N treatments. Highest N content(1.88% (grain) and 0.76% (straw)) and uptake (128.14 kg/ha) was recorded in T6 treatmentin all stages (tillering, PI and harvest) which was comparable with T8 and T9 treatment.